Ratio of specific heats (gamma) calculator for a mixture of different perfect gases - Lee, Siew Hui. (2013)
Ratio of Specific Heat, is an important thermodynamic property commonly used in the description of gaseous products. In this final year project, firstly the student will do a study on the background theory of the ratio of specific heats. Next, the student will design a fortran program named GAMMA which is able to assist the user in the calculation of the ratio of specific heat by inputting the temperature and gas conditions.